Applications of Nanoparticles in Treatment of Respiratory Disorders - Farah Deeba; Farzana Umer; Deep Nainan (Life and Science, 2021)
Respiratory disorders are very prevalent and high-incidence group of diseases having severe impacts on human health in the world. Some of the respiratory disorders are difficult to diagnose and treat, such as chronic obstructive pulmonary disease, asthma, lungs cancer, and pulmonary tuberculosis. Lungs cancer is the second most common cancer globally. Nano-delivery technologies have a great potential to improve the drug targeting in a specific area of infections in respiratory disease treatment. Not only nanoparticles concentrate the drug at specific-disease sites but also reduce the drug degradation and drug loss simultaneously. Sedimentation, nebulizers, carbon nanodots, and stimulus-responsive nanoparticles are currently being explored to use as a source for delivering nanodrugs to treat lungs cancer. Various nanoparticles such as steroids, salbutamol, liposome-mediated, and polystyrene are used in the treatment of asthma and preterm birth diseases. This study focused on different kinds of nanoparticles like gold, solid lipid nanoparticles (NPs), steroidal and liposome-mediated nanoparticles which are used to treat different pulmonary or respiratory disorders and also examine the current therapeutic techniques for the diagnosis of lung diseases and therapy using nanoscalebased inhalers.